Carbon Waste Powder Prepared from Carbon Rod Waste of Zinc-Carbon Batteries for Methyl Orange Adsorption - Fitria Rahmawati; Viona Natalia; Agung T. Wijayanta; Siti Rondiyah; Koji Nakabayashi; Jin Miyawaki (Bulletin of Chemical Reaction Engineering & Catalysis, 2020)
A research on the preparation of Carbon Waste Powder, CWP, was conducted and made from carbon rod waste which was extracted from used zinc-carbon batteries. This research was an effort to overcome environmental problem caused by battery waste by converting into adsorbent for methyl orange (MO) that frequently used by textile industries. The prepared powder was then analyzed to understand its characteristic peaks, crystallinity, and to compare the properties with other carbonaceous forms, i.e. a commercial Carbon Paper (CP), and a commercial meso- carbon micro-beads (MCMB). The analysis found that CWP is dominated by graphitic carbon. An adsorption experiment was then conducted to study their adsorption ability to methyl orange solution. The result found that those three carbonaceous materials have the ability to adsorb methyl orange with different activities. MCMB has the highest adsorption capacity of 0.197 mg.g-1. Meanwhile, CWP and CP show adsorption capacity of 0.066 mg.g-1 and 0.062 mg.g-1, respectively. Methyl orange adsorption on CWP and CP were under second order, which means the adsorption could be four times faster as the MO solution doubled. Moreover, the rate constant of MO adsorption on CWP is 8×10-4 min-1, which was higher than the rate constant of MO adsorption on CP. It confirmed that the CWP can be used as a promising adsorbent for dye waste water. Copyright © 2020 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).